Krause and Mahan's food & the nutrition care process - Raymond, Janice L.; Morrow, Kelly (Elsevier, 2021)
"A trusted classic for over 50 years, Krause and Mahan's Food & the Nutrition Care Process, 15th Edition presents the most up-to-date dietetics content available in this ever-changing field to ensure you provide optimal nutritional care. It offers cutting-edge, comprehensive coverage of a full range of dietetics topics, all in one book. You'll benefit from in-depth information from clinical specialists that provides practical and evidence-based recommendations related to nutrition assessment and intervention, nutritional needs of individuals in different stages of the life cycle, nutrition for health and fitness, and medical nutrition therapy"